Creativity in Children and Pupils With Dyslexia - Jan Viktorin (Ignatianum University Press, 2021)
This literature review analyzes ten specialized papers which focus on the issue of higher creativity among children and pupils with dyslexia. The aim of the article is to determine the level of creativity in this group, what may might affect the level of creativity among them, and whether there are significant differences in some areas between children and pupils with dyslexia and intact (typically developed) children and pupils. In connection with dyslexia, its possible advantages - and not only disadvantages - are beginning to be discussed, which are developing in the context of possible shortcomings. In children and pupils with dyslexia, increased creative potential and excellent visualization skills have been reported. Based on foreign research, a significantly higher level of creativity was not clearly demonstrated in children and pupils with dyslexia in comparison with intact children and pupils.